The Toy and the Twister - King-Cargile, Gillian (Book collections on Project MUSE., 2015)
"A fluff-brained bunny named Bear gets left outside during a storm. The only thing that can save him is science ... and a sassy doll named Sadie Scientist. Together, the toys get sucked into a tornado. Sadie helps Bear understand extreme weather and storm safety, but when they begin to fall, Bear has to think quickly to save his new friend"--